Knowledge Communication Strategy in Infrastructure Business - Widianingrum, Ratna (International Research Journal of Business Studies, 2023)
Infrastructure development is a program that usually includes mega projects and involves many stakeholders in its implementation, thus providing great opportunities for knowledge creation. However, the complexity that arises often prevents the creation of knowledge, either through the process of improving existing knowledge or through the process of discovering new knowledge. The process of changing knowledge through knowledge management to facilitate intra- and inter-organizational knowledge transfer has been discussed in various studies on knowledge management, but specific discussion on how to communicate strategies in knowledge management, especially in the infrastructure industry, is still sparse. This study aims to determine how the knowledge management process and public relations program actions in knowledge communication strategy can be adopted. The strategy will motivate systematic efforts to develop information and knowledge and create value in the future. The methodology used in this paper is searching for data and information through books, journals, and articles related to the topic. The results of this paper provide an understanding of the concepts and strategies of knowledge communication in knowledge management and its application to the infrastructure industry.